(3GdebOeI GdMVQejI aj Gdabg GdTGaYjs - (3GdMVQej, CaVd, YHO Gddg Hf YHO GdQMef Hf CHj HcQ, (B918 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj aQV YdjfG JYde TQGFY GdESdGe hHYO agPG eNJUQ dGHO dcd eSde ef eYQaJgs
(3BNQgG (B:s
(3aUd hjMQe JShjO GdTjH hhUd TYQg hJadjL GdCSfGf hGdhTe hGdMfG ddQLd HdG MGLg hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 96s
(3eYLe GdeDdajf (B2 / 249s
(3EjVGM Gdecfhf (B2 / 543s
(3gOjI GdYGQajf (B1 / 175s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs